Three-week schedule of irinotecan plus cisplatin in patients with previously untreated extensive-stage small-cell lung cancer - Hong, Y S (Nature Publishing Group, 2006)
Irinotecan and cisplatin demonstrated promising outcomes in extensive-stage small-cell lung cancer. According to the dosage and schedule of irinotecan, efficacy and toxicity profiles showed subtle differences. This study was designed to evaluate efficacy and toxicity of 3-week schedule of irinotecan/cisplatin in patients with previously untreated extensive-stage small-cell lung cancer. The primary objective was to evaluate response rate and secondary objectives were overall survival and progression-free survival. Patients with previously untreated extensive-stage small-cell lung cancer were enrolled. Irinotecan 65 mg m(−2) was administered on days 1 and 8 and cisplatin 60 mg m(−2) on day 1. Treatment was repeated every 3 weeks. Seven out of 54 patients (13.0%) had complete response, and partial response was observed in 33 (61.1%). The overall response rate was 74.1% (95% CI; 62.0–82.2%). Stable disease was observed in eight (14.8%) and no progressive disease was observed. After a median follow-up duration of 28.7 months, the median overall survival and progressive-free survival were 13.6 and 6.5 months, respectively. Major grade 3/4 toxicities were neutropenia (50.0%), anorexia (42.6%), diarrhoea (29.6%), fatigue (29.6%) and vomiting (13.0%). There was one treatment-related death owing to pneumonia. Three-week schedule of irinotecan/cisplatin showed effective antitumour activity and moderate toxicities in patients with previously untreated extensive-stage small-cell lung cancer.